Metode Internal Factor Evaluation (IFE) dan External Factor Evaluation (EFE) dalam Perencanaan Strategi Pendidikan Islam - Ainun Lutfiya (Al-Kindi, 2026)
Strategic planning is a crucial element in managing educational institutions to ensure the achievement of institutional vision, mission, and goals in a sustainable manner. This study aims to examine the role and contribution of the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) methods as strategic analysis instruments in educational strategic planning, particularly in Islamic education. This research employed a qualitative approach using a library research method. Data were collected from various academic sources, including strategic management and education textbooks, scholarly journal articles, and relevant academic documents. Data analysis was conducted using descriptive qualitative analysis and content analysis through the processes of categorizing, comparing, and synthesizing information to address the research questions. The findings indicate that the IFE method is effective in identifying internal strengths and weaknesses of educational institutions, while the EFE method plays a significant role in analyzing external opportunities and threats. The integration of IFE and EFE provides an objective and measurable basis for determining an institution’s strategic position and formulating development, maintenance, or improvement strategies. Therefore, IFE and EFE serve as essential foundations for adaptive, contextual, and quality-oriented strategic decision-making in Islamic education.